Expenditures on medications in Paraíba and compliance with Constitutional Amendment n° 29/2000 - Labara Andrade de Carvalho, Marisa; de Mendonça Lima, Tácio; Rodrigues Martins de Freitas, Gabriel (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To investigate the expenses allocated to medications and Public Health Actions and Services (ASPS) reported in the Health Public Budget Information Sys-tem (SIOPS) by municipalities in Paraíba and the compliance with Constitutional Amendment (EC) nº 29/2000 by the federative entities. Methods: This is a cross–sectional, documentary, and descriptive study. The data collected through SIOPS refer to the period from 2018 to 2022. The investigation adopted in this work comprises the agreement between the declared municipal data, the correspondence of information regarding the compliance with EC-29/2000 in Paraíba, and the com-parison between the amounts spent on health and medications. Results: The results revealed that spending on medications corresponds, on average, to 2% of the total health expenditure by the municipalities, and that an increase in the “Total Health Expenditure” indicator does not necessarily affect the “Medication Expenditure” indicator. Furthermore, the spending on ASPS by the municipalities exceeds the minimum required by Complementary Law No. 141/2012, differing from the State and the Union, which do not exceed the minimum required by legislation. Conclusions: Thus, the burden of financing health care on the municipalities of Paraíba is recognized. Despite their lower revenue and financial constraints, they meet legal requirements above the limit. However, it is urgent to correct disparities in resource distribution to ensure continuous improvements in the local health system.